Influence of Cation Order and Valence States on Magnetic Ordering in La2Ni1−xMn1+xO6. Issue 11 (11th June 2019) - Nasir, Mohd.; Khan, Mahmud; Bhatt, Subhash; Bera, Anup Kumar; Furquan, Mohammad; Kumar, Sunil; Yusuf, Sk. Mohammad; Patra, Nirmalendu; Bhattacharya, Dibyendu; Jha, Shambhu Nath; Liu, Shun‐Wei; Biring, Sajal; et al.
Abstract : Among multifunctional double perovskite oxides, La2 NiMnO6 has recently drawn significant attention due to its importance both in terms of understanding of fundamental physics and potential for device applications. The relative alteration in Ni:Mn ratio strongly influences the structural and magnetic properties of La2 NiMnO6 . The cation ratio and degree of cation order significantly affect the magnetic coupling of the two B‐site cations in these compounds. In the present study, La2 Ni1− x Mn1+ x O6 ( x = −0.25, 0, 0.25) samples with different Ni:Mn ratio have been prepared using sol–gel method and modifications of the above physical properties from that of a stoichiometric sample of La2 NiMnO6 are discussed. The crystalline structures of the samples varied with different ionic ratios. While all samples exhibited ferromagnetic behavior, long‐range Ni/Mn magnetic ordering was detected in selected samples only. The experimental values of saturation magnetization were smaller than the theoretical spin‐only moments, which suggests a less ordered state for all samples. Due to an increased antiferromagnetic interaction caused by antisite disorders, the saturation magnetization decreases while the coercive field increases with decreasing Mn content. Abstract : Polycrystalline La2 Ni1− x Mn1+ x O6 samples with different Ni:Mn ratio are prepared using sol–gel method. All samples are ferromagnetic in nature. Cation ordering is higher for Mn‐rich samples. The LN75M125 sample shows largest saturation moment, Ms ≈5.65 μ B /f.u.